Motivation and guidance of college students’ low-carbon behavior: evidence from Chinese colleges and universities - Ren, Gaofei; Liu, Changjin; Chen, Yaoyao (Frontiers in Psychology, 2024)
In the context of the global implementation of the emission peak and carbon-neutral strategic goal, guiding residents' low-carbon behavior is of great significance for the realization of the dual carbon goal. However, existing studies have paid less attention to the low-carbon behavior of college students. Based on the theory of planned behavior, this paper constructs a theoretical model of influencing factors of college students' low-carbon behavior. Combined with 612 questionnaires from Chinese colleges and universities, this study uses a structural equation model and multi-group analysis method to explore the motivation of college students' low-carbon behavior and guiding education strategies. The results show that low-carbon attitude, subjective norms, lowcarbon values, and perceived behavior control have significant positive effects on low low-carbon behavior intention of college students, and influence their low-carbon behavior through low-carbon behavior intention. Further research found that gender and growth environment (urban vs rural) presented heterogeneity in different influence paths, and the perceived cost had a significant negative moderating effect during the transition from low-carbon intention to low-carbon behavior. These research findings provide a theoretical basis and policy inspiration for explaining and guiding the low-carbon behavior of college students.emission peak and carbon neutrality, college students, low-carbon behavior, motivation and guidance, theory of Planned Behavior